(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2018)
This article discusses the development of the administration of Islamic Law in the northern states of Peninsular Malaysia from the pre-Independence period until after Independence,with specific focus on laws regarding the provisions for inheritance. Using doctrinal analysis methodology, this article highlights the issues related to the uneven evolution of Islamic laws regarding inheritance from 1952 until 2016 in these states. The discrepancies betweenthe Islamic Administration Enactments and state enactments are presented in a table outlining the differences in terms of amendment, improvement andrepeals in accordance with the requirements of the mainstream.The findings show that there is no dynamic change in the laws regarding inheritance and its administration from the pre-independence era until now, often resulting in inheritance-related conflicts. Keywords: estate property, Northern States of Peninsular Malaysia, Administration of Islamic Law.